2008
DOI: 10.1002/elps.200800098
|View full text |Cite
|
Sign up to set email alerts
|

Ion separation in nanofluidics

Abstract: Ionic species with a constant charge-to-size ratio (i.e. electrophoretic mobility) cannot be separated in electroosmotic or pressure-driven flow along microscale channels. In nanoscale channels, however, the enormous electric fields inside electrical double layers cause transverse ion distributions yielding charge-dependent mean ion speeds in the flow. Those ions with a constant charge-to-size ratio can thus be separated solely by charge (or equivalently, size) in nanofluidics. Here we develop an analytical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…19,20 For example, ion transport with d / λ D ( d = channel critical dimension) ratios ranging from 1 to 10 show anomalous transport behavior, such as charge-dependent ion mobilities due to transverse electromigration (TEM) resulting from solute/wall electrostatic effects. 15,2123 Pennathur and Santiago showed that electrokinetic separations in nanoslits were dependent on ion valence, ζ (zeta potential), ion mobility, and λ D . 15,21 Garcia et al 24 reported the electrokinetic separation of Alexa 488 (negatively charged) and rhodamine B (neutral) fluorescent dyes in glass-based nanochannels with widths between 35 and 200 nm.…”
mentioning
confidence: 99%
“…19,20 For example, ion transport with d / λ D ( d = channel critical dimension) ratios ranging from 1 to 10 show anomalous transport behavior, such as charge-dependent ion mobilities due to transverse electromigration (TEM) resulting from solute/wall electrostatic effects. 15,2123 Pennathur and Santiago showed that electrokinetic separations in nanoslits were dependent on ion valence, ζ (zeta potential), ion mobility, and λ D . 15,21 Garcia et al 24 reported the electrokinetic separation of Alexa 488 (negatively charged) and rhodamine B (neutral) fluorescent dyes in glass-based nanochannels with widths between 35 and 200 nm.…”
mentioning
confidence: 99%
“…Finally, the normalized plate height and resolution are computed for a prescribed value of the species Peclet number, Pe i , using Eqs. (20) and (22).…”
Section: à8mentioning
confidence: 97%
“…Despite this continued interest, however, only a few studies [16][17][18][19] have reported the capabilities of the process, as measured by peak resolution, and only a handful have addressed the factors that determine this. Xuan [20] derived governing equations for both electroosmotic and pressure-driven flows and presented solutions for the resolution as a function of the channel height relative to the Debye thickness. He showed that resolution for the optimum speed exhibited a maximum at some optimum value of this normalized channel height that depends on the charge and that the maximum resolution for cations was generally much higher than for anions.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Unlike MOFs, which have coordinated structures, COFs are solely fabricated with organic constructing units via strong covalent bonding; therefore, they possess superior chemical stability in acidic media and organic solvents, thus interacting with targets in a wide pH range. [25][26][27] Moreover, due to uniform-sized nanopores and large surface area, COFs exhibit high capacity, fast adsorption, and good regenerability and accessibility. [28][29][30][31] In virtue of the abovementioned observations, we infer that COFs possess great potential as ideal adsorbents for the enrichment of organic compounds via SPE pre-treatment.…”
Section: Introductionmentioning
confidence: 99%